2015
DOI: 10.5114/wiitm.2015.56407
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic approach in the treatment of large epiphrenic esophageal diverticulum.

Abstract: Epiphrenic diverticulum of the lower third of the esophagus is a relatively rare disorder. We present the case of a large, 7.5 cm diameter esophageal epiphrenic diverticulum treated by the laparoscopic approach. Surgery was indicated by the severity of the patient‘s symptoms and size of the diverticulum. A laparoscopic transhiatal diverticulectomy with a myotomy and Dor fundoplication was carried out. The overall operative time was 180 min. The patient tolerated the surgery well and was discharged from hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
10
1
2
Order By: Relevance
“…( 2 - 4 ) In the United States prevalence of this disease is approximately 15/100,000. ( 5 ) This disease treatment depends on intensity of symptoms and risk of potential complications such as bleeding and perforation. Currently, diverticulectomy with cardiomyotomy and laparoscopic fundoplication is the chosen surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…( 2 - 4 ) In the United States prevalence of this disease is approximately 15/100,000. ( 5 ) This disease treatment depends on intensity of symptoms and risk of potential complications such as bleeding and perforation. Currently, diverticulectomy with cardiomyotomy and laparoscopic fundoplication is the chosen surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Divertículos esofagianos, embora raros, devem sempre ser considerados como diagnóstico diferencial em casos de disfagia, halitose e enfermidades respiratórias por broncoaspiração (1) .Os divertículos de esôfago mais comuns são aqueles de pulsão, ou falsos divertículos, geralmente localizados no terço proximal ou no terço inferior, sendo comumente causados por aumento de pressão intra-esofagiana, secundário a distúrbios de motilidade ou obstrução.Por outro lado, divertículos de tração, ou divertículos verdadeiros, geralmente são pequenos, sintomáticos em até 20% dos pacientes e localizados a até dez centímetros da junção esôfago gástrica, estão presentesem homens 60-70 anos de idade,adquiridosecausados por sequelas de doenças pulmonares ou mediastinais (2) . Quando sintomáticos, os divertículos podem causar disfagia, regurgitação, halitose e rouquidão.…”
Section: Introductionunclassified
“…There are various options of surgical approaches for MIS such as VATS, laparoscopy or combined VATS and laparoscopy. According to previously published literatures, most surgeons preferred the laparoscopic approach (1,(3)(4)(5)7). Laparoscopic approach is useful for performing the myotomy across the LES and the antireflux procedure.…”
Section: A B Cmentioning
confidence: 99%
“…Recently, as the development of surgical techniques and instruments of minimally invasive surgery (MIS), many surgeons have attempted minimally invasive surgeries for epiphrenic esophageal diverticula. They reported that MIS for epiphrenic esophageal diverticula was a safe and feasible approach which had many advantages (1,(3)(4)(5)(6). There are various options of surgical approaches for MIS of epiphrenic diverticula such as video-assisted thoracoscopic approach, laparoscopy or combined thoracoscopy and laparoscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation